An inexpensive solution for motion analysis. (September 2014) - Hansen, Clint; Gibas, David; Honeine, Jean-Louis; Rezzoug, Nasser; Gorce, Philippe; Isableu, Brice
This study investigated the reliability of the recently released low-cost NaturalPoint OptiTrack 250e camera system across different measurement designs. Results are compared to an already well-established motion capture system from Vicon Motion Systems Ltd (Oxford, UK). The OptiTrack performed well across measurement conditions. Provided with the AMASS software kit from C-Motion (Germantown, MD, USA), nine distances from three rigid bodies (ten markers) were used to calculate measurement accuracy. Independent t-tests, a one-way multivariate analysis of variance, intra-class correlation coefficients, and the standard error of measurement were computed for all conditions to evaluate the differences and the reliability of the systems. The results suggest that the NaturalPoint OptiTrack 250e camera system is a reliable working system that can certainly be used in biomechanics and other related fields.